Synthesis and characterization of magnetic ZnCl2-activated carbon produced from coconut shell for the adsorption of methylene blue - Yağmur, Hatice Karaer; Kaya, İsmet (Journal of molecular structure, 2021)
•Magnetic particles as a adsorbent was produced from coconut shell with low cost material.•Magnetic particles were successfully coated on active carbon surface.•MACz obtained from AC by loading iron oxide was used to remove of MB from aqueous solutions. In this research, a magnetic-activated carbon composite was synthesized to investigate its adsorption to methylene blue dye. Active carbon (ACz) was produced by ZnCl2 activation of coconut shell (char: ZnCl2, 2:1). Magnetic activated carbon (MACz) was prepared via an easy method by chemical co-precipitation of Fe3+/Fe2+. The pore diameter, pore-volume, and surface area of MACz were determined from N2 adsorption isotherms. The ACz and MACz were characterized by several techniques such as BET, SEM/EDX, FT-IR, XRF, VSM, TGA, and pHpzc analysis. The average particle size, particle size distribution, and zeta potential of MACz were determined by Zetasizer. The zero point charge of the MACz was determined as approximately 4.9 pH. Moreover, the adsorption by MACz was investigated as kinetically and thermodynamically for removal of methylene blue (MB) from aqueous solution. The kinetics and thermodynamic parameters were also calculated. According to the results, the adsorption process was determined as endothermic. The Langmuir and Freundlich isotherms models were used and it was found that adsorption of MB onto MACz best fitted to Freundlich model according to RMSE, SSE, and R2 values. The maximum adsorption capacity of the composite was calculated as 156.25 mg/g. Thermodynamic parameters (ΔHo, ΔGo, and ΔSo) were also calculated, which revealed that the adsorption process is spontaneous.